Economic evaluation of integrated new technologies for health and social care: Suggestions for policy makers, users and evaluators. (November 2016) - Wildman, John; McMeekin, Peter; Grieve, Eleanor; Briggs, Andrew
Abstract: With an ageing population there is a move towards the use of assisted living technologies (ALTs) to provide social care and health care services, and to improve service processes. These technologies are at the forefront of the integration of health and social care. However, economic evaluations of ALTs, and indeed economic evaluations of any interventions providing both health benefits and benefits beyond health are complex. This paper considers the challenges faced by evaluators and presents a method of economic evaluation for use with interventions where traditional methods may not be suitable for informing funders and decision makers. We propose a method, combining economic evaluation techniques, that can accommodate health outcomes and outcomes beyond health through the use of a common numeraire. Such economic evaluations can benefit both the public and private sector, firstly by ensuring the efficient allocation of resources. And secondly, by providing information for individuals who, in the market for ALTs, face consumption decisions that are infrequent and for which there may be no other sources of information. We consider these issues in the welfarist, extra-welfarist and capabilities frameworks, which we link to attributes in an individual production model. This approach allows for the valuation of the health component of any such intervention and the valuation of key social care attributes and processes. Finally, we present a set of considerations for evaluators highlighting the key issues that need to be considered in this type of economic evaluation. Highlights: Investigates economic evaluations where health and outcomes beyond health are valued. Introduces a new economic evaluation method. Combines health, capabilities, health production, welfarism and extra-welfarism. Suggestions to guide economic evaluations in order to benefit the public sector. Highlights importance of economic evaluations for the private ALT market.